JOB ENGAGEMENT AND ITS IMPACT ON CITIZENSHIP BEHAVIOR ANALYTICAL RESEARCH IN THE IRAQI MINISTRY OF EDUCATION - Zaid Ali Shidikh, DR. hakem Hassouni almaialy (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The current research aims to test the relationship of the effect of Job Engagement and its factors (sharing information, sharing power, rewards and incentives) in the behavior of organizational citizenship and its factors (altruism, civility, sportsmanship, conscience, and voluntary participation) at the Ministry of Education and the directorates of education in Baghdad Governorate, as well as standing On the level of interest of the directorates researched in the search variables and their factors, and there is no doubt that the search variables are important for the ministry and the directorates and the research sample, given the challenges and rapid changes in the course of events, especially Job Engagement, and what citizenship behavior can provide to the directorates under discussion, so the research problem in identifying At the level of practice and interest, and the ability of directorates to employ factors of functional integration in the behavior of organizational citizenship, opinions of a class intentional class (138) views were obtained from workers in the Ministry of Education and directorates of Baghdad Governorate and who occupied the position of (general managers, assistants of general managers, heads of departments, Directorates of the directorates, and their assistants). The researcher employed the descriptive exploratory approach, and used the questionnaire as a main tool to collect data and identify the level of The application and the relationship between the two research variables. The sample responses were subject to descriptive and inferential statistical analysis via the AMOS V.25 & SPSS V.25 programs. For the purpose of data processing, the researcher used statistical methods (ratios and repetitions, mean, mean, standard deviation, relative importance, coefficient of difference Relative, confirmatory and exploratory factor analysis, natural distribution, simple correlation coefficient (Pearson, simple and multiple regression coefficient), and statistical analysis has led to the availability of Job Engagement and its factors, as well as the Ministry of Education's use of Job Engagement to enhance citizenship behavior.